Kontribusi Ekonomi Islam Dalam Pembangunan Ekonomi Nasional - Anisa Dwi Safitri; Ria unani; July, July Wulandari; Heri, Heri Irawan; Vania, Vania Audina (Journal of Economics and Business, 2024)
ABSTRACT Islam as a universal, integral and comprehensive system of life has established a complete order for human life, which includes political, economic, educational, artistic, social, cultural and other aspects. As a way of life, Islam organizes everything related to life, from the simplest things to the most complicated matters. Both in political economic, educational, artistic, social, cultural, etc. aspects. Islam is a perfect religion, which regulates matters related to the economy. If a country's economy applies the Al-Quran and Hadith as the basis for its implementation, of course a national economy will run well and in a direction. The IM economic system was created so that Muslims could continue to carry out economic activities that were free from all bad qualities such as usury, wrongdoing, ikhtikar, haram and many more. However, in reality, not all Muslim countries in the world have implemented this basis. Furthermore, this article explains how Islamic economics contributes to national economic development, especially Indonesia as the country with the largest Muslim base in Asia. ABSTRAK Islam sebagai sistem kehidupan yang universal, integral, dan menyeluruh telah menetapkan tatanan kehidupan manusia yang utuh, meliputi aspek politik, ekonomi, pendidikan, seni, sosial, budaya, dan lainnya. Sebagai pedoman hidup, Islam mengatur segala sesuatu yang berkaitan dengan kehidupan, dari hal yang paling sederhana hingga hal yang paling rumit. Baik dalam aspek politik, ekonomi, pendidikan, seni, sosial, budaya, dan lain sebagainya. Islam adalah agama yang sempurna, yang mengatur hal-hal yang berkaitan dengan perekonomian. Jika perekonomian suatu negara menerapkan Al-Quran dan Hadits sebagai landasan pelaksanaannya, tentu perekonomian nasional akan berjalan  dengan baik dan terarah. Sistem perekonomian IM diciptakan agar umat Islam dapat tetap menjalankan kegiatan ekonomi yang terbebas dari segala sifat buruk seperti riba, zalim, ikhtikar, haram dan masih banyak lagi. Namun kenyataannya, belum semua negara Islam di dunia menerapkan landasan tersebut. Lebih lanjut, artikel ini menjelaskan bagaimana ekonomi Islam berkontribusi terhadap pembangunan ekonomi nasional, khususnya Indonesia sebagai negara dengan basis umat Islam terbesar di Asia.